ARca, Pengembangan Buku Interaktif Berbasis Augmented Reality dengan Smartphone Android - Andria Kusuma Wahyudi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
This paper focuses on ARca, an interactive book as a learning medium diintegerasikan with augmented reality to improve student interest in learning the Prambanan temple. In this study using the book as a medium that elicits information of 3D models that represent real objects Prambanan temple, audio, animation, and additional text as complementary information. ARca is designed with engineering-based markerless thus become more attractive user interface. ARca developed using virtual buttons which the user can interact with the physical book through touch on the book. This paper emphasizes the concepts and previous research, and evaluation of its prototype.